(untitled) (Journal of the Management Sciences, 2025)
The paper examined the strength of SDGs as global inclusive development framework in Nigeria as a third world country. Inclusive development requires collective commitment to accessibility, participation, accountability, and resources from various nations and communities. Though, the initiative is comprehensive, integrative, and participatory with focus on equality, however, there are doubt that its implementation may not differ from the previous, including MDGs. The paper adopted descriptive analysis and relied on secondary data to evaluate the implementation, examine the challenges and identify the way forward towards achieving most of the goals’ target. The finding from the review of data as contained in Sustainable Development Report 2024 on the Nigeria’s Achievement Trend (AT) in each of the seventeen (17) goals are qualitatively classifies into moderately improving with 29 % of goals, stagnating with 47% goals, decreasing with 12% goals, and information unavailable 12% of goals respectively. The result shows that Nigeria performed significantly low in most of the goals. By 2024, the Nigeria’s SDGs Ranking is 146/166, though, Spillover ranking is 16/166. The identified challenges threatening the implementation include; effects of global effects on less developed nations, poor funding, unreliable data and corruption with implications for national policy decisions. Moving forward, the government needs to increase funding, aligning national policies with the SDGs targets and sustaining implementation evaluation.